Consumer acceptance of omega-3 enhanced beef in surveys and retail trials - Curran, Kassie (Kansas State University, 2015)
This study examines consumer acceptance of omega-3 enhanced beef using data from a choice experiment and a retail trial. The retail trial was conducted in collaboration with La Vaca Meat Company, Littleton, CO which offered omega-3 enhanced beef products for sale both online and in-store. Prices were adjusted periodically, and online customers were surveyed to gather information about their purchase decisions. The choice experiment was included in an online survey conducted with a nationally representative sample of consumers. One version of the survey focused on ground beef and another focused on steak. Within each version separate treatments examined the impact of providing information about how levels of the most beneficial omega-3s could be enhanced in beef. The choice experiment evaluated how variation in meat attributes such as omega-3 content, safety, and tenderness influenced purchase decisions. Data from the choice experiment were analyzed using multinomial logit models. Results indicate that overall acceptance and willingness to pay for omega-3 enhanced beef was below that of grass-fed beef. Additional information about omega-3s increased willingness-to-pay for enhanced omega ground beef, but had no impact on willingness-to-pay for enhanced omega steak. The analysis showed significant heterogeneity in preferences, and, in particular, females had significantly higher willingness-to-pay for grass-fed ground beef than males. Average willingness-to-pay for grass-fed steak was estimated at $3.69/lb above conventionally raised product, compared to an estimated premium of $1.86/lb for enhanced omega steak. For ground beef the average premium for grass-fed product was estimated to be $1.27/lb compared to $0.79/lb for the enhanced omega product.
Keywords: Consumer; Consumer acceptance; Beef; Omega-3 fatty acids; Choice experiment; Agriculture, General (0473); Animal Sciences (0475); Economics, Agricultural (0503)